AUTHENTICATION SCHEME USING PCCP AND GBAS TECHNIQUES - Priyanka Navgire; Mandar Kshirsagar; Namrata Kale (International Journal of Innovations in Engineering Research and Technology, 2021)
In Information security or in computer security, user authentication has most important or essential areas. Most of the web application offers knowledge based authentication which contains alphanumeric passwords as well as graphical passwords. Graphical password plays an important part for user in security point of view. Existing system has security for authentication in cloud by using graphical passwords which has some limitation as username in text format. Proposed system, provided better authentication to the username or user-id by using PCCP (Pervasive Cued Click Point) technique as well as password by using GBAS(Grid Based Authentication) technique.